Analisis Volume, Kecepatan, dan Kepadatan Lalu Lintas dengan Metode Greenshields dan Greenberg - Widodo, Wahyu; Wicaksono, Nur; Harwin, Harwin (Jurnal Semesta Teknika, 2012)
The creation of a transportation system that ensures the movement of people, vehicles, or goods in a smooth, safe, fast, cheap, convenient, and environmentally friendly way has been the goal of country development. An increase in traffic volume will cause a change in traffic behavior. Theoretically, there is a fundamental relationship between the flow, speed, and density of traffic. Activities and land use will affect the performance of a variety of roads. Land in Jalan Wates Km 5 is used as commercial and market area that is the center of the crowd. The purpose of this study was to determine: speed, traffic volume, density, capacity, and the relationship between speed, volume and density using Greenshields and Greenberg methods, degree of saturation, and level of service. The study was conducted in one day. The result showed that the capacity of the road is still able to accommodate the volume of existing traffic.